Efeito da aplicação de sistemas adesivos autocondicionantes associados ao laser Nd:YAG na prevenção do desgaste erosivo/abrasivo do esmalte dental - Crastechini, Érica [UNESP] (2014)
The aim of this study was to evaluate the effectiveness of the Nd: YAG laser, alone or associated with different auto constraints adhesive systems, in the prevention of erosive and abrasive wear of the dental enamel. A hundred and sixty samples of bovine enamel were prepared, polished and subjected to an initial erosion in 0.3 % citric acid solution for 5 min. The initial profiles of the enamel surface were measured using a profilometer, whose unit is measured in micrometers (μm). The samples were randomly divided into eight groups (n = 20): SB - Single Bond Universal (3M/Espe) adhesive application and light curing; SB+L - Single Bond Universal adhesive application, Nd:YAG laser irradiation (80 mJ, 10 Hz) and light curing; FB - Futura Bond U (Voco) adhesive application and light curing; Group FB+L - Futura Bond U adhesive application, Nd:YAG laser irradiation and light curing; GEN - G-aenial Bond (GC) adhesive application and light curing; GEN+L - G-aenial Bond adhesive, Nd:YAG laser irradiation and light curing; L - Only Nd:YAG laser irradiation; C - No treatment (control group). The erosive challenge, using citric acid 0.3 % (pH 2.6) for 2 min, and abrasive challenge, using a tooth brushing machine (40 cycles, load of 200 g) with toothpaste diluted in artificial saliva (1:3 wt/wt), were performed. Four cycles a day were performed during 5 days. The profiles of the enamel surfaces were again measured using the profilometer. Data were analyzed using analysis of variance (ANOVA) and Tukey statistical tests. The level of significance was 5%. When ANOVA (one factor) test was applied, it was observed statistical difference (p=0,0000) of surface wear. Mean values (± SD) and results of the Tukey test were: GEN – 4,88 (±1,09) a; L – 5,04 (±0,99) a; FB - 5,32 (±0,93) ab; GEN + L – 5,46 (±1,27) abc; SB + L – 5,78 (±1,12) abc; FB + L – 6,23 (±1,25) bc; SB - 6,35 (±1,11) c; C .....